2018
DOI: 10.12717/dr.2018.22.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Localization NUCB2/nesfatin-1 in the Liver and Heart of Mouse Fetus

Abstract: NUCB2/nesfatin-1 is first known to be expressed in the hypothalamus while controlling appetite and energy metabolism. However, recent studies have shown that NUCB2/nesfatin-1 was expressed in the various organs as well as the hypothalamus. Our previous reports also demonstrated that NUCB2/nesfatin-1 was expressed in the ovary, testis, pituitary gland, lung, kidney, and stomach of fetal and adult mice. However, the role of NUCB2/nesfatin-1 in mouse fetus remains unknown. Thus, the aim of this study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Nucb2 also participates in other biological processes, e.g., adipogenesis [39] , biomineralization [40] and carcinogenesis [41] , [42] . Additionally, Nucb2 is ubiquitously expressed in the central nervous system [38] and peripheral tissues, such as the digestive tract [43] , reproductive system [44] , pancreas [45] , [46] , and heart [47] . The multifunctionality of Nucb2 may result from its structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nucb2 also participates in other biological processes, e.g., adipogenesis [39] , biomineralization [40] and carcinogenesis [41] , [42] . Additionally, Nucb2 is ubiquitously expressed in the central nervous system [38] and peripheral tissues, such as the digestive tract [43] , reproductive system [44] , pancreas [45] , [46] , and heart [47] . The multifunctionality of Nucb2 may result from its structure.…”
Section: Introductionmentioning
confidence: 99%
“…NUCB2/NESF-1-like immunoreactivity was observed in cytoplasmic vesicles of cells in peripheral tissues, including gastric cells 29 and rat Leydig cells 30 . NUCB1 mRNA and nesfatin-1 immunoreactivity was reported in embryonic and adult mouse liver, suggesting a local role for these peptides 31 . NUCB1 and NUCB2 mRNA and their proteins were upregulated in NESF-1- and NLP-treated HepG2/C3A cells, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Nesfatin-1, an 82 amino acid peptide hormone derived from post-translational processing of the N-terminal of NUCB-2, is a potent anorexigenic hormone and reduces appetite and weight gain in both mice and humans [ 36 , 37 ]. Nesfatin-1 is expressed in several peripheral organs such as the liver, stomach, kidney, lungs, small intestine, large intestine, and the heart [ 36 , 37 , 38 ]. It has been demonstrated that HFD reduced serum levels of Nesfatin-1 in male C57BL/6J mice [ 39 ].…”
Section: Discussionmentioning
confidence: 99%